(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because they would be running on lesser power but also most likely without the support of a central system, potential ubiquitous computing gadgets would need to interface with other smart devices on an ad hoc basis. However, no one communication technique has yet to emerge as a viable contender in the area of ubiquitous computing: numerous present wireless communication methods seem to be deficient in robustness, use excessive levels of energy, or need the utilization of networks to be competitive. We installed a Smart device into the first iteration of a multi sensor device connected as part of a National Smart-Its research project, which was built to assess the suitability of the newest but also most potential Bluetooth module for particular connection requirements. Despite the reality that Bluetooth allows for reliable and easy ad hoc communication, preliminary research suggests that the Bluetooth system might benefit from better support for asymmetrical communication and, in especially, slave to-slave transmission.